2020
DOI: 10.3233/jnd-200478
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Physical Activity Using Accelerometers in Youth with Duchenne Muscular Dystrophy

Abstract: Background: Physical activity, assessed by accelerometers, has been proposed as a quantitative outcome measure for patients with DMD, but research is limited Objective: To assess the total amount and patterns of physical activity in patients with DMD using accelerometers. Methods: Physical activity was assessed in patients with DMD (n = 49, 13.6 ± 4.0-year-old) and age-and sex-matched healthy controls (n = 15, 14.0 ± 2.3-year-old) using wrist-and ankle-worn accelerometers. To assess the amount of activity, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Participants wore a wrist-watch triaxial accelerometer (GENEACTIV, Kimbolton, Cambs, United Kingdom) over a consecutive 7 day period [ 53 ], which has been reported as reliable and valid previously [ 54 , 55 ]. All participants wore accelerometers on the wrist to increase adherence and remove the potential discomfort of waist-worn accelerometers for non-ambulant participants [ 56 ]. Furthermore, the use of accelerometers to assess sleep has shown 83–89% agreement with polysomnography [ 57 , 58 ], and has become a more common assessment method due to participant convenience compared to polysomnography [ 59 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants wore a wrist-watch triaxial accelerometer (GENEACTIV, Kimbolton, Cambs, United Kingdom) over a consecutive 7 day period [ 53 ], which has been reported as reliable and valid previously [ 54 , 55 ]. All participants wore accelerometers on the wrist to increase adherence and remove the potential discomfort of waist-worn accelerometers for non-ambulant participants [ 56 ]. Furthermore, the use of accelerometers to assess sleep has shown 83–89% agreement with polysomnography [ 57 , 58 ], and has become a more common assessment method due to participant convenience compared to polysomnography [ 59 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, one longitudinal study on CMT patients found that measuring walking activity with SAM was more sensitive than 6MWT in detecting disease progression at 12 months [24]. The content and discriminant validity of ActiGraph, a triaxial accelerometer mounted on an elastic belt around the waist, was demonstrated in different NMDs (ALS, DMD) [25][26][27][28], although criterion validity was not verified against manual step count in CMD patients, possibly because of gait impairment [29]. Finally, two studies explored the psychometric properties of the 95th percentile of stride velocity (SV95C), measured by Actimyo, in ambulant DMD patients [30,31].…”
Section: Continuous Monitoring Of Pa With Inertial Sensorsmentioning
confidence: 99%
“…Physical Behaviour monitoring was successfully completed by all participants over 7 days, with 0 non-wear time. The tri-axial accelerometers were worn on the wrist rather than hip or thigh in order to increase adherence, as demonstrated in MD and non-MD populations [19,31,32].…”
Section: Accelerometermentioning
confidence: 99%
“…Recently, SB has been shown to occupy 83-89% of waking hours in a mixed group of ambulatory and nonambulatory adults with MD, compared to 59% SB time in healthy controls [18]. The inclusion of both ambulatory and non-ambulatory adults with MD may be problematic in the assessment of SB, as SB time is known to be 20% lower in non-ambulatory compared to ambulatory boys with Duchenne MD (SB time = 91% in Non-Ambulant, and 71% in Ambulant) [19]. In addition to SB determined through METs, advances in accelerometry have now allowed posture classification, time spent Sitting or Standing in waking hours, to be identified [20], which has only previously been reported (9.1 Hours) using self-report methods in ambulant adults with MD [21].…”
Section: Introductionmentioning
confidence: 99%